Identification of 24 Unknown Substances (NIAS/IAS) from Food Contact Polycarbonate by LC-Orbitrap Tribrid HRMS-DDMS3: Safety Assessment - Vicent Yusà; Antonio López; Pablo Dualde; Olga Pardo; Igor Fochi; Pablo Miralles; Clara Coscollá (International Journal of Analytical Chemistry)
Twenty-four substances, mainly NIAS, have been tentatively identified in food contact polycarbonate through the application a new, fast, and automated analytical strategy for the investigation of unknowns in food contact materials. Most of the identified compounds were plasticizers, slip agents, antioxidants, and ultraviolet stabilizers and fragrances, and the majority of them have not been previously identified in PC food contact materials. The workflow setup includes an intelligent data acquisition applied using LC-Orbitrap Tribrid-HRMS (MS3), with an automated data processing using Compound DiscovererTM. To obtain a high confidence identification of unknown substances, a very strict criterion has been established, which comprises exact mass, isotopic profile, MS2 match, retention time, and MS3 match. To check for the safety of the migration from the food contact polycarbonate, a risk assessment was achieved using the threshold of the toxicological concern (TTC) approach. Except for the slip agent hexadecanamide, the compounds tentatively identified do not represent a risk.